O mito do cárcere ressocializador - Silva, Anaclara Pedroso Fernandes Valentim da (2018)
The resocializing purpose of the penalty, in the course of history, has been placed as its primary purpose. This claim is supported by the fact that some of the dogmatic theories on the subject never exclude it as the ultimate goal of the sanction or even place it as a limitation on other purposes, as for example in Claus Roxin's Dialectic Theory. Moreover, the Brazilian legal system, if analyzed in a systematic way, prioritizes re-education and social reintegration of the convicted in society, which demonstrates crystal proof because the Law on the Execution of Criminal Sanctions contains numerous resocializing mechanisms to be applied. The purpose of this study is to analyze, through the hypothetical-deductive method, whether the hypothesis of resocialization of the condemned prisoner is a myth, besides being essentially obedient to the guiding values of the national legal system and likewise being a motivating purpose of numerous legal institutes included in the Law on the Execution of Criminal Sanctions. Thus, it was verified that social integration is not really implemented, either because it is not in fact the purpose of the intended penalty or because of the dysfunctional use of the available legal instruments, it became only a legitimating speech of the existence of the sentence and has as a consequence the mistaken production of legal and legislative decisions, impacting significantly on the criminal policy adopted by the State